La conciencia semántica en el desarrollo del lenguaje oral de los niños del primer grado básico, del jardín de infantes Dr. Fernando guerrero cantón Riobamba, provincia de Chimborazo, período lectivo 2014-2015 - Guamán Auquilla, Zoila Susana (2016)
This study analyzes the importance of semantic awareness in the oral language development in children from 4 to 5 years old. For this, the problem statement is determined, where there are problems regarding with language, the general objective is to determine how the semantic consciousness favors language development and the specific which is able to be achieved at the end of the investigation, it is justified because it is important and it will help children, relevant in learning about the social impact and the beneficiaries of the research are children from 4-5 years, in the theoretical framework is scientifically based, where it is considered important to take the quotes from the authors of philosophy, epistemological, psychological, pedagogical and legal foundation, theoretically where it could be known concepts of the two variables under study, definition of basic terms related to the subject, in the methodology we worked with the descriptive field, with a qualitative approach, using tools such as observation to children of First Grade of Basic Education at the Kindergarten Dr. Fernando Guerrero, Riobamba canton, Chimborazo province. Once collected the information we proceeded to tabulate the data and present them using statistical charts with their analysis and interpretation. The results determine the specific needs that children have in order to improve verbal phonological, syntactic and semantic fluency. Finally, conclusions are drawn up based on the specific objectives and recommendations, with supporting documents and literature in the annexes.